Structural variability of Aleppo pine stands in two forests in northeastern Algeria - Malika Rached Kanouni; Insaf Hani; Ratiba BOUSBA; Amina Beldjazia; Hichem KHAMAR (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rached-Kanouni M, Hani I, Bousba R, Beldjazia A, Khammar H. 2020. Structural variability of Aleppo pine stands in two forests in northeastern Algeria. Biodiversitas 21: 2848-2853. The layout of the stand can be described as the width of the trees, their reciprocal locations, diametric distinction and height. The goal of this study is to recognize changes in the Pinus halepensis spatial and demographic systems in two Beni Oudjana and Chettaba Forests, located in northeast Algeria. An inventory of trees in these forest formations with P. halepensis dominance was carried out based on dendrometric parameters such as total height, tree diameter at dbh ? 5 cm, basal area, total volume, etc., as well as the number of trees in the forest. Tree diameter and height measurements were made on 12 rectangular plots (20 m × 20 m), located in both forests. The results obtained show that the mean stand density, mean diameter, basal area and total volume are higher in Chettaba Forest, the values attributed to these parameters are respectively (422 trees/ha, 27.07 cm, 26, 86 m2, 251.63 m3); while the total height and regeneration rate show significantly higher values in Beni Oudjana Forest (18.97 m, 607 individuals/ha). The structure in diameter and height of the species is bell-shaped to asymmetrically positive with a predominance of small diameter individuals in the Chettaba forest. On the other hand, in the Beni Oudjana Forest, the structure is ‘L’ shaped, showing a predominance of very small diameter individuals. These results indicate that the low regeneration rate of P. halepensis in the Chettaba Forest is due to anthropogenic pressures that favor the degradation of this forest.